NaLi-H1: A universal synthetic library of humanized nanobodies providing highly functional antibodies and intrabodies - Moutel, Sandrine; Bery, Nicolas; Bernard, Virginie; Keller, Laura; Lemesre, Emilie; de Marco, Ario; Ligat, Laetitia; Rain, Jean-Christophe; Favre, Gilles; Olichon, Aurélien; Perez, Franck (eLife, 2016)
In vitro selection of antibodies allows to obtain highly functional binders, rapidly and at lower cost. Here, we describe the first fully synthetic phage display library of humanized llama single domain antibody (NaLi-H1: Nanobody Library Humanized 1). Based on a humanized synthetic single domain antibody (hs2dAb) scaffold optimized for intracellular stability, the highly diverse library provides high affinity binders without animal immunization. NaLi-H1 was screened following several selection schemes against various targets (Fluorescent proteins, actin, tubulin, p53, HP1). Conformation antibodies against active RHO GTPase were also obtained. Selected hs2dAb were used in various immunoassays and were often found to be functional intrabodies, enabling tracking or inhibition of endogenous targets. Functionalization of intrabodies allowed specific protein knockdown in living cells. Finally, direct selection against the surface of tumor cells produced hs2dAb directed against tumor-specific antigens further highlighting the potential use of this library for therapeutic applications. Antibodies are proteins that form part of an animal’s immune system and can identify and help eradicate infections. These proteins are also needed at many stages in biological research and represent one of the most promising tools in medical applications, from diagnostics to treatments. Traditionally, antibodies have been collected from animals that had been previously injected with a target molecule that the antibodies must recognize. An alternative strategy that uses bacteria and bacteria-infecting viruses instead of animals was developed several decades ago and allows researchers to obtain antibodies more quickly. However, the majority of the scientific community view these “in vitro selected antibodies” as inferior to those produced via the more traditional approach. Moutel, Bery et al. set out to challenge this widespread opinion, using a smaller kind of antibody known as nanobodies. The proteins were originally found in animals like llamas and camels and are now widely used in biological research. One particularly stable nanobody was chosen to form the backbone of the in vitro antibodies, and the DNA that encodes this nanobody was altered to make the protein more similar to human antibodies. Moutel, Bery et al. then changed the DNA sequence further to make billions of different versions of the nanobody, each one slightly different from the next in the region that binds to the target molecules. Transferring this DNA into bacteria resulted in a library (called the NaLi-H1 library) of bacterial clones that produce the nanobodies displayed at the surface of bacteria-infecting viruses. Moutel, Bery et al. then screened this library against various target molecules, including some from tumor cells, and showed that the fully in vitro selected antibodies worked just as well as natural antibodies in a number of assays. The in vitro antibodies could even be used to track, or inactivate, proteins within living cells. The NaLi-H1 library will help other researchers obtain new antibodies that bind strongly to their targets. The approaches developed to create the library could also see more people decide to create their own synthetic libraries, which would accelerate the identification of new antibodies in a way that is cheaper and requires fewer experiments to be done using animals. These in vitro selected antibodies could help to advance both fundamental and medical research.